Diseminasi Penggunaan Sosial Media dalam Perluasan Sebaran Pemasaran pada Produk UMKM - Widia, Elsa (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The impact of the COVID-19 pandemic on MSMEs is believed to be greater due to the high level of vulnerability due to changes in people's lifestyles. Several policies carried out by the government, such as large-scale social restrictions (PSBB), a ban on going home and the recommendation to "stay at home" are aimed at reducing the number of spread of this virus. However, this situation also has an economic impact on the income of business actors, especially MSMEs. In the midst of this situation, digital marketing is a way out that can become the main strategy in expanding the market. In this community service, we focus on training MSMEs in Agam Regency, West Sumatra Province in the field of digital technology through social media platforms. This strategy is believed to be very effective in expanding the market and strengthening branding. This service activity was carried out in November 2020, through training methods and social media creation practices. The result of this activity is that around 80% of MSMEs have used social media and are able to create persuasive messages. MSMEs have also paid special attention to strengthening product branding. This training can be continued with the creation of e-commerce for a wider marketing reach.